How anticipatory action can empower women in disaster-prone areas - Myers, Emily; Kosec, Katrina; Kyle, Jordan; Quisumbing, Agnes R.; Gonzales, Teresa; Madero, Ana; Mittrick, Caitlin; Rapadas, Amica (International Food Policy Research Institute, 2024)
As the planet warms, climate-driven disasters are becoming more frequent and severe worldwide. These events pose increased risks to vulnerable communities and groups, particularly women and girls, who face disproportionate challenges in their aftermath. Disasters often exacerbate existing gender inequalities—limiting women’s access to food and essential services, reducing their physical safety and decision-making power, and increasing time poverty. These impacts, compounded by gendered social norms, make recovery from disaster significantly harder for women.